Modulatory Effects of Astragalus Polysaccharides on T-Cell Polarization in Mice with Polymicrobial Sepsis. (26th November 2015) - Hou, Yu-Chen; Wu, Jin-Ming; Wang, Ming-Yang; Wu, Ming-Hsun; Chen, Kuen-Yuan; Yeh, Sung-Ling; Lin, Ming-Tsan
Abstract : Background. This study evaluated the impact of different doses of Astragalus polysaccharides (APS) on the functional status and phenotype of T cells during polymicrobial sepsis. Methods. On day 1 after cecal ligation and puncture, mice were treated with either saline, 100 (A100), 200 (A200), or 400 mg APS/kg body weight (BW) (A400) by an intraperitoneal injection daily for 4 days. All mice were sacrificed 5 days after the operation. Results. APS treatment reversed the sepsis-induced decrement in the T helper (Th) cell population, and the percentage of activated Th cells also increased in the spleen and Peyer's patches. APS administration downregulated the percentages of circulating Th2 cells and regulatory T cells (Treg), and the percentage of Th17 cells in blood was upregulated in the A400 group. Weight loss and kidney injury were attenuated in the A100 and A200 groups but not in the A400 group at the end of the study. Conclusions. Treatments with 100 and 200 mg APS/kg BW reduced Treg populations and elicited a more-balanced Th1/Th2 response that consequently attenuated immunosuppression in polymicrobial sepsis. High-dose APS administration led to excessive responses of Th17 cells which may have adverse effects in sepsis-induced organ injury.